Answer:
1) x = 5√(1-sin^2t)
2) y = = -2+3t
Explanation:
1)
Given rectangular equation:
x^2/25 + y^2 =1
Parametric equations y=-sint and x=?
Find parametric equation for x
Substituting value of y =-sint in given rectangular equation, we get
x^2/25 + (-sint )^2 =1
x^2/25 + sin^2t =1
x^2 + 25sin^2t = 25
x^2 =25 - 25sin^2t
taking square root on both sides
x= √(25 - 25sin^2t)
= √25(1-sin^2t)
= 5√(1-sin^2t)
2)
Given rectangular equation:
y=-3x+4
Parametric equations x=2-t and y=?
Find parametric equation for y
Substituting value of x=2-t in given rectangular equation, we get
y= -3(2-t) +4
= -6+3t+4
= -2+3t !